الصداع التوتري وعلاقته بخفض الصحة النفسية لدى أساتذة التعليم الثانوي دراسة ميدانية ببعض ثانويات ولاية تيارت - روبي, محمد; بن هني, مونة (Université de M'sila, 2018)
الملخص: هدفت الدراسة إلى الكشف عن طبيعة العلاقة الموجودة بين الصداع التوتري وتدهور الصحة النفسية لدى أساتذة التعليم الثانوي، وكذلك الكشف عن الفروق بين متوسط درجات أساتذة التعليم الثانوي على مقياس الصداع التوتري ومقياس الصحة النفسية تبعا للمتغيرات التالية: (الجنس-التخصص- الأقدمية)، وتألفت العينة من (140) فرد من مختلف التخصصات لمعظم ثانويات ولاية تيارت للموسم الدراسي (2014/2015)، ولتحقيق هذا الهدف تم استخدام الأدوات التالية: مقياس الصداع التوتري المعد من قبل زينب شقير(2003) والذي تم إعادة بنائه على البيئة الجزائرية ومقياس الصحة النفسية المعد من قبل الباحثان، وتم التحقق من صدق المقياسين وثباتهما. وأسفرت نتائج الدراسة على مايلي: - وجود علاقة ارتباطية بين درجة الصداع التوتري ودرجة الصحة النفسية لدى اساتذة التعليم الثانوي عند مستوى الدلالة (0.01). - عدم وجود فروق في درجة الصداع التوتري تعزى لمتغير الجنس ومتغير الأقدمية لدى أساتذة التعليم الثانوي. - وجود فروق في درجة الصداع التوتري ودرجة الصحة النفسية تعزى لمتغير التخصص لدى أساتذة التعليم الثانوي عند مستوى الدلالة (0.05) لصالح الأدبيين. - عدم وجود فروق بين متوسط درجات أساتذة التعليم الثانوي على مقياس الصحة النفسية تُعزى إلى متغير الجنس والأقدمية. Abstract: The study aimed at discovering the nature of the relationship that between tension headaches and the mental health of high school teachers, as well as detect the differences between the high school teachers degrees on the tension-type headaches measeres with the mental health following the veraibles: (sex, speciality, time work experience), The sample was composed form (140) individuals from the different specialities of the mojority of the high schools in Tiaret, during the school year )2014- 2015(, and to achieve this purpose, we use these tools; tension-type headaches Scale prepared by "Zaineb Cheghir) 2003( it was reconstructed on to the Algerian environment, and also the mental health Scale prepared by the researchers, both of the validity and consistency measurements were checked and validated. The results are: - The existence of correlation between the tension-type headaches degree and mental health level of high school teachers on (0.01). - The abscence of differences in tension-type headaches degree is related to sex variable and variable seniority of high school teachers. - The existence of differences in tension-type headaches degree is related to speciality variable of high school teachers (0.05) for the litterary teachers. - The abscence of differences between the medum and mental health degrees of high school teachers on mental health is related to sex and seniority variable.
Keywords: الصداع التوتري، الصحة النفسية، أساتذة الثانوي. Tension headaches, Mental health